Clinicopathologic Factors of Cervical Adenocarcinoma Stages IB to IIB. Issue 9 (November 2015) - Mabuchi, Yasushi; Yahata, Tamaki; Kobayashi, Aya; Tanizaki, Yuko; Shiro, Michihisa; Ota, Nami; Yagi, Shigetaka; Minami, Sawako; Ino, Kazuhiko
Abstract : Objective: The aim of this study was to clarify the clinicopathologic factors of stages IB to IIB cervical adenocarcinoma. Methods: Several clinicopathologic factors were compared between 35 patients who underwent radical hysterectomy and pelvic lymphadenectomy due to cervical adenocarcinoma stages IB to IIB and 77 patients with squamous cell carcinoma (SCC). Results: In patients with adenocarcinoma, univariate analysis demonstrated that International Federation of Gynecology and Obstetrics stage, tumor size, and lymphovascular space invasion were significantly associated with progression-free survival (PFS), whereas FIGO stage, lymphovascular space invasion, and lymph node metastasis were significantly associated with overall survival (OS). However, multivariate analysis revealed that FIGO stage was the only significant factor for PFS in patients with adenocarcinoma. In patients with SCC, univariate analysis demonstrated that FIGO stage and lymph node metastasis were significantly associated with PFS, whereas FIGO stage, lymphovascular space invasion, and lymph node metastasis were significantly associated with OS. Multivariate analysis revealed that lymph node metastasis was the only significant factor for PFS and OS in patients with SCC. In 26 patients who were positive for high-risk human papillomavirus (HPV), including both adenocarcinoma and SCC patients, univariate and multivariate analyses revealed that HPV18 was significantly associated with poorer PFS compared with non-HPV18. There was a significant difference in distribution of HPV genotype between adenocarcinoma and SCC. Conclusions: Careful treatment may be necessary for the patients with lymphovascular space invasion in early-stage cervical adenocarcinoma. The presence of HPV18 may have an influence on the prognosis of early-stage cervical carcinoma.